1986
DOI: 10.1111/j.1527-3466.1986.tb00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Cibenzoline

Abstract: Cibenzoline succinate [4,5-dihydro-2-(2,2-diphenylcyclopropyl)imidazole butanedioate (1:l) salt] is a new antiarrhythmic drug. It is not chemically related to other known antiarrhythmic agents ( Fig. 1) and is the first imidazoline derivative known to have antiarrhythmic activity. The molecular weight of cibenzoline succinate is 380, and its empiric formula is CI8Hl8N2-C4H6O4. Cibenzoline has also been referred to in the literature with the trade names Cipralan@, RitmalanB, and Pracizolinem and the industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It has been shown, e.g., that relatively high and fairly consistent bidisomide plasma concentrations could be sustained in anesthetized dogs using loadimaintenance dosing [ Gartliwaite et al., 19921, including prolonged "drips" of 50.07 nig/kg/rnin [Hackett et al, 19931. In contrast, minutes after infusing 4 mg/kg of cibenzoline into dogs, plasma concentrations <2 pgirnl have been observed [Sassine et al, 19841, suggesting that in dogs more "hrisk" maintenance infiisions of this drug may be necessary. Plasma concentrations of parent drug achieved in these experiments at the low doses of propafenone, bidisomide, disopyratnide, and cibenzolinc would result in ECG, electropliysiologic, and/or antiarrhythmic effects in humans [Naccarella et al, 1984;Dangman and Miura, 1986;Lynch and Horowitz, 1991;Steiirer et al, 1991;Moreno et al, 1992;Page et al, 1992;Roy et al, 19921. The CO experiments showed that propafenone was inore potent than the other three agents in its general cardiovascular effects in addition to its antiarrhythmic effects. Since the 3 pgiml plasma concentration of propafenone resulted in a 47% decrease in CO, it seems likely that higher concentrations, had we achieved them, might have been poorly tolerated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown, e.g., that relatively high and fairly consistent bidisomide plasma concentrations could be sustained in anesthetized dogs using loadimaintenance dosing [ Gartliwaite et al., 19921, including prolonged "drips" of 50.07 nig/kg/rnin [Hackett et al, 19931. In contrast, minutes after infusing 4 mg/kg of cibenzoline into dogs, plasma concentrations <2 pgirnl have been observed [Sassine et al, 19841, suggesting that in dogs more "hrisk" maintenance infiisions of this drug may be necessary. Plasma concentrations of parent drug achieved in these experiments at the low doses of propafenone, bidisomide, disopyratnide, and cibenzolinc would result in ECG, electropliysiologic, and/or antiarrhythmic effects in humans [Naccarella et al, 1984;Dangman and Miura, 1986;Lynch and Horowitz, 1991;Steiirer et al, 1991;Moreno et al, 1992;Page et al, 1992;Roy et al, 19921. The CO experiments showed that propafenone was inore potent than the other three agents in its general cardiovascular effects in addition to its antiarrhythmic effects. Since the 3 pgiml plasma concentration of propafenone resulted in a 47% decrease in CO, it seems likely that higher concentrations, had we achieved them, might have been poorly tolerated.…”
Section: Discussionmentioning
confidence: 96%
“…The reduction in SV atid CO caused by cibenzoline, then, seems likely to be diie to an increase in end-systolic volume resulting from negative inotropisin [F'erdouw et al, 1982;van den Brand et al, 1984;Dangman and Miura, 1986;Humen et al, 1987;Matsuokaet al, 19911. Bidisoinide caused an increase in end-diastolic pressure at 15 nig/kg i.v. in dogs [Frederick et al, 19891, but did riot significantly &ect left ventricular systolic pressure in the same experiments. Bidisomide only modcstly reduced inax dPidt in vivo and developed tension of papillary muscles in vitro [Frederick et al, 19891.…”
Section: Discussionmentioning
confidence: 98%